The study of key issues about integration of GNSS and strong-motion records for real-time earthquake monitoring. Issue 3 (1st August 2016) - Tu, Rui; Zhang, Pengfei; Zhang, Rui; Liu, Jinhai
Abstract: This paper has studied the key issues about integration of GNSS and strong-motion records for real-time earthquake monitoring. The validations show that the consistence of the coordinate system must be considered firstly to exclude the system bias between GNSS and strong-motion. The GNSS sampling rate is suggested about 1–5 Hz, and we should give the strong-motion's baseline shift with a larger dynamic noise as its variation is very swift. The initialization time of solving the baseline shift is less than one minute, and ambiguity resolution strategy is not greatly improved the solution. The data quality is very important for the solution, we advised to use multi-frequency and multi-system observations. These ideas give an important guide for real-time earthquake monitoring and early warning by the tight integration of GNSS and strong-motion records.